Evaluation of dairy slurry as an alternative of organic fertilizer in African star grass - Elizondo-Salazar, Jorge Alberto (2021)
The mix of residues originating from animal production systems, which can include manure, cleaning water, rainwater, and waste feed, have been used to improve crop productivity, and are commonly referred to as slurry. The objective of this study was to evaluate the effect of the application of inorganic and organic fertilizers on the production and chemical composition of African star grass in a specialized dairy farm. The study was carried out from May to December 2018 at the Alfredo Volio Mata Experiment Station of the University of Costa Rica. An area of 500 m2 was used in an African star grass paddock. The total area was divided into three blocks and each block was subdivided into four plots that corresponded to the different nitrogen fertilization treatments at a constant dose of 250 kg/ha/year distributed in six applications. Each plot was 5 x 5 m and the treatments were: 1) control (0 kg of nitrogen), 2) compost, 3) slurry and 4) urea. Total yield of green forage was similar for the control and compost treatment (3,8 and 3,9 ton/ha/cut) surpassed by the slurry and urea treatment (5,7 and 7,5 ton/ha/cut, respectively). There were no significant differences (p>0.05) for dry matter concentration (19,7 to 21,6%), while dry matter yield was significantly higher (p<0.001) in urea (1,2 ton/ha/cut), followed by slurry and compost (0,9 and 0,7 ton/ha/cut, respectively). Treatment with urea presented the highest yield and the best nutritional characteristics followed by the slurry treatment, which represents a viable alternative of organic fertilizer to be used in African star grass.